Peran Asimetris Spillover Indeks Syariah Cina terhadap Indeks Syariah Indonesia Selama Pilpres 2024 - Iqbal Rafiqi; Aliyatul Hasanah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The Islamic financial market is becoming increasingly integrated globally, including the China Sharia Index and the Indonesia Sharia Index. However, in certain situations such as the 2024 presidential election, market dynamics may experience asymmetric spillover effects. High political uncertainty during the election has the potential to increase risks and volatility, altering the transmission pattern of information from the Chinese market to Indonesia disproportionately. This study aims to examine the influence of the China Sharia Index on the Indonesia Sharia Index during the 2024 presidential election and to analyze the role of asymmetric spillover. The research method employed is a quantitative approach using daily secondary data. Analysis was conducted through simple linear regression after passing classical assumption tests, which indicated that the data is normally distributed, with no heteroscedasticity and no autocorrelation. The results show that the China Sharia Index has a positive and significant influence on the Indonesia Sharia Index with an R Square of 81.4%. Spillover is stronger during a market downturn, indicating an asymmetric effect. Political uncertainty during the 2024 election strengthens investor responses to negative risks, making political and economic stability crucial for the resilience of Indonesia's Islamic capital market.